Nurse Communication, Quality of Health Services, and Its Relationship with Patient Satisfaction in Inpatient Ward - Heltty, Heltty; Zahalim, Zahalim; Krismiadi, Dedi (Jurnal Kesehatan Metro Sai Wawai, 2025)
Nurses are among the healthcare workers who play a crucial role in enhancing patient satisfaction. Communication plays an essential role in implementing nursing care to deliver high-quality services that ensure patient satisfaction with the care they receive. Patient satisfaction is a key indicator of the quality of nursing services in hospitals. The study aims to determine the relationship between nurse communication and the quality of health services, with a focus on increasing patient satisfaction, in the inpatient rooms of Muna Barat Hospital. The type of research used is quantitative research with a correlational design; the population in this study was patients in the inpatient room of Muna Barat Hospital. The samples selected for this study employed a random sampling technique. A total of 81 respondents participated in this study. The data analysis method used the Chi-Square test using a significance level of 0.05. The Chi-Square test obtained a p value = 0.001 which indicates that there is a relationship between nurse communication and patient satisfaction at Muna Barat Hospital. Meanwhile, in the Quality of Health Services, a p-value of 0.002 was obtained, indicating that there is a relationship between the Quality of Health Services and patient satisfaction at Muna Barat Regional Hospital. The results of the phi coefficient test also showed a low and positive patterned relationship between nurse communication and patient satisfaction (Ⴔ=0.310), quality of health services and patient satisfaction (Ⴔ=0.336). Nurse communication and Quality of Health Services are related to Increasing Patient Satisfaction. Patient satisfaction as consumers who receive nursing services is an essential component in improving the quality of nursing services. A nurse needs to implement effective communication in providing surgical procedures, as good communication leads to patient satisfaction with the service received.